2022
DOI: 10.1152/ajpheart.00398.2021
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in rat renal arterial responses following exercise training

Abstract: During aerobic exercise, hemodynamic alterations occure; while blood flow in skeletal muscle arteries increases, it decreases in visceral vessels due to mesenterial vasoconstriction. However, maintaining renal blood flow during intensive sport is also a priority. Our aim was to investigate the changes of vascular reactivity and histology of isolated renal artery of male and female rats in response to swim-training. Wistar rats were distributed into four groups: male sedentary (MSed), male trained (MTr), female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…After exercise training, the non-selective COX-dependent vasoconstriction remained in males, but not in females. Regarding vasodilatation, the results were the same between the two vessels [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After exercise training, the non-selective COX-dependent vasoconstriction remained in males, but not in females. Regarding vasodilatation, the results were the same between the two vessels [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the gracilis arteriole, tangential wall stress and norepinephrine-induced contraction were elevated in female rats compared to in male animals [ 11 ]. During the examination of a visceral large artery (renal artery), we found that phenylephrine-induced vasoconstriction was reduced in males, but not in females [ 12 ]. The effect of sex hormones on blood vessels is well-known.…”
Section: Introductionmentioning
confidence: 99%